Identification and Quantification of Microplastics in Aquaculture Environment - Xiang, Shuo; Xie, Yuqun; Sun, Xuemei; Du, Hao; Wang, Jun (Frontiers in Marine Science, 2022)
The existence of MPs poses potential threat to the entire ecosystem and has gained wide public attention. As an essential source of aquatic products, aquaculture industries are inevitably subjected to MPs pollution, particularly when plastic products are widely applied in aquaculture. Even so, the identification of MPs in aquaculture is rarely reported. Hence high-efficient analytical methods for accurate MPs detection in aquaculture environment is of utmost significance. This review comprehensively summarizes the analytical methods for MPs in aquaculture, including sampling, extraction, and qualitative and quantitative analysis of MPs. MPs are identified and quantified mainly by visual inspection, spectroscopy, or thermal analysis. In addition, this review also points out the limitations of these methods and the accuracy of quality control. Finally, the need for establishing standard methods is emphasized and suggestions for future research are also put forward.